"Mining is like a search and destroy mission": The case of Silver City. Issue 3 (2nd October 2019) - Kvam, August; Willett, Jennifer
ABSTRACT: While mines are often thought of as a driving force for development, this may not be the case due to power discrepancies between companies and local communities, as well as lack of protection provided by the government. In response, communities have begun to challenge mining companies. The industry itself has countered by developing negotiation techniques to gain local support. This study contributes to the literature on mining and ecosocial work practice, by drawing on the case of Silver City Nevada, where the broad consensus in the community is that the positive local-level impact of mining activities is negligible.